Role of macrophage in intervertebral disc degeneration - Yiming Dou; Yiming Zhang; Yang Liu; Xun Sun; Xinyu Liu; Bin Li; Qiang Yang (Bone Research)
Abstract Intervertebral disc degeneration is a degenerative disease where inflammation and immune responses play significant roles. Macrophages, as key immune cells, critically regulate inflammation through polarization into different phenotypes. In recent years, the role of macrophages in inflammation-related degenerative diseases, such as intervertebral disc degeneration, has been increasingly recognized. Macrophages construct the inflammatory microenvironment of the intervertebral disc and are involved in regulating intervertebral disc cell activities, extracellular matrix metabolism, intervertebral disc vascularization, and innervation, profoundly influencing the progression of disc degeneration. To gain a deeper understanding of the inflammatory microenvironment of intervertebral disc degeneration, this review will summarize the role of macrophages in the pathological process of intervertebral disc degeneration, analyze the regulatory mechanisms involving macrophages, and review therapeutic strategies targeting macrophage modulation for the treatment of intervertebral disc degeneration. These insights will be valuable for the treatment and research directions of intervertebral disc degeneration.